2014
DOI: 10.3892/ol.2014.2781
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical staining of tumor necrosis factor-α and interleukin-10 in benign and malignant ovarian neoplasms

Abstract: Ovarian cancer is the ninth most common malignancy and the fifth leading cause of cancer death in women in the USA. The majority of malignant tumors of the ovary are diagnosed at an advanced stage, making it the most fatal gynecological cancer. The aim of the current study was to determine whether there are differences in immunohistochemical tissue staining of cytokine tumor necrosis factor-α (TNF-α) and interleukin-10 (IL-10) between benign tumors and malignant primary ovarian cancer. In total, 28 patients un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 30 publications
0
16
1
2
Order By: Relevance
“…In a small series of 25 cases, Takayama and colleagues showed positive TNF-α staining in 80% by immunohistochemistry but in only 35% by ISH suggesting non-specific immunoreactivity in the tumor cells[34]. Similarly, the distribution of TNF protein was noted to be different from that of TNF mRNA in a study by Naylor et al that showed majority of TNF protein localized to the stroma or the epithelial-stromal interface[35, 36] Others have used immunohistochemistry to evaluate expression of inflammatory markers, including TNF-α, IL-1, IL-6, IL-10, TGFβ and COX2, but have been limited either by high background on immunohistochemical staining[37] small sample size with a broad mix of benign and malignant ovarian tumors[38] or by lack of well annotated clinical data in order to detect significant epidemiological associations. TNF-α has also been evaluated in ovarian cancer by gene expression arrays but these are limited by their inability to distinguish between TNF-α expression by tumor cells versus tumor infiltrating inflammatory cells[19].…”
Section: Discussionmentioning
confidence: 99%
“…In a small series of 25 cases, Takayama and colleagues showed positive TNF-α staining in 80% by immunohistochemistry but in only 35% by ISH suggesting non-specific immunoreactivity in the tumor cells[34]. Similarly, the distribution of TNF protein was noted to be different from that of TNF mRNA in a study by Naylor et al that showed majority of TNF protein localized to the stroma or the epithelial-stromal interface[35, 36] Others have used immunohistochemistry to evaluate expression of inflammatory markers, including TNF-α, IL-1, IL-6, IL-10, TGFβ and COX2, but have been limited either by high background on immunohistochemical staining[37] small sample size with a broad mix of benign and malignant ovarian tumors[38] or by lack of well annotated clinical data in order to detect significant epidemiological associations. TNF-α has also been evaluated in ovarian cancer by gene expression arrays but these are limited by their inability to distinguish between TNF-α expression by tumor cells versus tumor infiltrating inflammatory cells[19].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Charles et al demonstrated that chronic production of TNF‐α in the tumor microenvironment increases myeloid cell recruitment and consequently tumor growth in vivo. Previous studies demonstrated an increase of TNF‐α protein and gene expression in human OC compared with non‐malignant controls . High ascitic TNF‐α protein levels have previously been found to be associated with poor survival in univariate analyses, however, data concerning intra‐tumor TNF‐α expression and clinical outcome are not available.…”
Section: Discussionmentioning
confidence: 99%
“…High ascitic TNF‐α protein levels have previously been found to be associated with poor survival in univariate analyses, however, data concerning intra‐tumor TNF‐α expression and clinical outcome are not available. In line with previous data, we demonstrate high levels of TNFA in human OC compared with non‐malignant control tissues . However, we were unable to determine a significant prognostic effect of TNFA expression in OC patients.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α has been demonstrated to possess anti-tumor activity as it has cytostatic and cytotoxic effects on a number of cancer cell lines (2). However, previous studies have demonstrated that TNF-α may also affect matrix degradation and mediate the development of tumor metastases (3,4). Additionally, TNF-α regulates the expression levels of cell adhesion proteins and therefore may serve a role in determining the metastatic phenotype of tumor cells (5,6).…”
Section: Introductionmentioning
confidence: 95%